2008
DOI: 10.1523/jneurosci.3142-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathic Pain Memory Is Maintained by Rac1-Regulated Dendritic Spine Remodeling after Spinal Cord Injury

Abstract: Localized increases in synaptic strength constitute a synaptic basis for learning and memory in the CNS and may also contribute to the maintenance of neuropathic pain after spinal cord injury (SCI) through the de novo formation or elaboration of postsynaptic dendritic structures. To determine whether SCI-induced dendritic spine remodeling contributes to neuronal hyperexcitability and neuropathic pain, we analyzed spine morphometry, localization, and functional influence in dorsal horn (DH) neurons in adult rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
156
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(170 citation statements)
references
References 56 publications
11
156
2
1
Order By: Relevance
“…A small slit was made in the atlanto-occipital membrane, between the base of the skull and spinal vertebra C1 and a 32 gauge catheter was threaded caudally to the lumbar enlargement and secured by suturing. To prevent CSF leakage and infection, the rostral opening was heat sealed by pinching the exposed tip with a sufficiently heated forcep (Tan et al, 2008). The catheter tip location was confirmed within the intrathecal space after the animals were killed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A small slit was made in the atlanto-occipital membrane, between the base of the skull and spinal vertebra C1 and a 32 gauge catheter was threaded caudally to the lumbar enlargement and secured by suturing. To prevent CSF leakage and infection, the rostral opening was heat sealed by pinching the exposed tip with a sufficiently heated forcep (Tan et al, 2008). The catheter tip location was confirmed within the intrathecal space after the animals were killed.…”
Section: Methodsmentioning
confidence: 99%
“…Only a few studies have investigated the possibility of morphological alterations of postsynaptic structures within second-order sensory neurons in diabetes as an underlying mechanism for diabetic neuropathic pain (Yamano et al, 1986;Malone et al, 2008). Our previous work has shown that structural alterations of synaptic spines within dorsal horn neurons can have adverse functional implications (Tan et al, 2009a), which may contribute neuropathic pain in spinal cord injury (SCI) and peripheral nerve injury (Tan et al, 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, not all moderately contused rats developed allodynia, although the reported incidence varies from 20% (Nesic, et al, 2005), to 50% (Drew et al, 2004), to 100% (Tan et al, 2008). To determine the number of SCI rats that developed allodynia after SCI, we first established a cutoff criterion for discriminating the mechanical sensitivity of SCI rats that displayed painful behavior from spontaneous fluctuations in mechanical sensitivity among uninjured rats.…”
Section: Novel Analysis Of the Allodynia In Sci Ratsmentioning
confidence: 99%
“…Various studies in experimental animals uncovered a mosaic of injury-induced molecular and cellular changes in segments caudal to a SCI (Krenz and Weaver, 1998;Ballermann and Fouad, 2006;Kitzman, 2006Kitzman, , 2007Soares et al, 2007;Hou et al, 2008;Tan et al, 2008;Hou et al, 2009;Boulenguez et al, 2010;Murray et al, 2010;Ichiyama et al, 2011;Singh et al, 2011;Kapitza et al, 2012;Tan et al, 2012). Depending upon the SCI model and specific functional assessments, these alterations in the properties of neuronal circuits have alternatively been classified as beneficial or detrimental.…”
Section: Introductionmentioning
confidence: 99%